Decision Support System in The Distribution of Direct Village Cash Assistance (BLT DD) in Bunga Mas Kelurahan, Seluma Regency Using Simple Multi Attribute Rating Technique (SMART) Algorithm - Ujang Juhardi; Diana Diana; Dandi Sunardi; Jefri Maulana Handika Siregar (Penerbit Jurnal Indonesia, 2023)
Dana Desa as described in Article 1 paragraph 8 of the Regulation of the Minister of Finance No. 190/PMK.7/2021 is a fund sourced from the state revenue and expenditure budget intended for Villages which is transferred through the district/city regional revenue and expenditure budget and is used to finance government administration, development implementation, community development, and community empowerment. Village BLT itself is budgeted for at least 40% of the ceiling value of the Village Fund received by each Village as regulated in Presidential Regulation No. 104 of 2021. For BLT Village recipients, it is regulated in Article 33 paragraph (1) of the Minister of Finance Number 190/PMK.07/ 2021. However, there are not a few mistakes and injustices in receiving BLT Desa. Decision Support System (DSS) is a system that can provide a reference in making decisions based on mathematical calculations of the values ​​of the determining criteria. Therefore, it is necessary to create a